FROM SOFT BALANCING TO BANDWAGONING: CONTEMPORARY BRAZIL–US RELATIONS IN SOUTH AMERICA - Rinaldi, Augusto (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
Using the soft balancing concept and a comparative methodology, I analyze the diplomatic strategies mobilized by Brazil towards the US in South America from 2003 to 2022. The empirical results suggest that in the last two decades, Brazil moved away from the role of “soft balancer” during Lula’s and Rousseff’s mandates (2003–2016) to a “tactical convergence” in Temer's (2016–2018) to “bandwagoning” in Bolsonaro's (2019–2022). The main drivers for these different strategies are domestic and regional changes. Approaching this thematic contributes to a better understanding of Brazilian regional priorities and abilities to deal with the US in the region.